Preparation characterisation of alumina nanocomposites. (2018) - Charvani, S.; Reddy, S. Shravan Kumar; Narendar, G.; Gopal Reddy, Ch.
Abstract: To meet the industrial requirements of light weight and high strength materials, lot of research work is going on worldwide for improvement of properties of light weight non-metallic composites. Researchers are trying to meet the industrial requirements by adding nanoparticles in preparation of composite materials and making nanocomposites. Nanocomposites are formed by mixing two or more dissimilar materials and adding nanoparticles in the matrix in order to control and develop new and improved properties of composites. The properties of composites depend not only upon the individual components used but also upon the morphology and the interfacial characteristics of the constituents and nanoparticles added. In the present investigation, laminates of epoxy resin and nanoparticles of Al2 O3 as filler are used with Aramid fibre, hybrid of Carbon and Aramid fibre as reinforcement are prepared. The nanoparticles, in the proportion of 1%, 3% and 5% are loaded into the composites. Nanoparticles of Al2 O3 of 20-30nm size are first dispersed into methanol by mechanical stirring. The solution is further sonicated for effective dispersion of nanoparticles. The mixture of methanol and Al2 O3 nanoparticles are mixed in Epoxy resin and mechanically stirred and sonicated. During mixing some of the methanol is evaporated. Further, the remaining methanol is removed by heating and drying. Then, Hardener is mixed with the mixture of epoxy- Al2 O3 and laminates are prepared. The laminates are cut to the required size of test samples for testing mechanical properties. It is observed that the mechanical properties are improved with the addition of nanoparticles of Al2 O3 . The SEM images of nanocomposites formed with 5% nanoparticle loading with Plane composites, Aramid, Carbon, hybrid of Aramid and Carbon composites shows that good bonding is formed between the fibre and resin mixed with nanoparticles.